Study of the number of occlusal contacts in maximum intercuspation before orthodontic treatment in subjects with Angle Class I and Class II Division 1 malocclusion - Gustavo Adolfo Watanabe-Kanno; Jorge Abrão (Dental Press Editora, 2012)
OBJECTIVE: Define and compare numbers and types of occlusal contacts in maximum intercuspation. METHODS: The study consisted of clinical and photographic analysis of occlusal contacts in maximum intercuspation. Twenty-six Caucasian Brazilian subjects were selected before orthodontic treatment, 20 males and 6 females, with ages ranging between 12 and 18 years. The subjects were diagnosed and grouped as follows: 13 with Angle Class I malocclusion and 13 with Angle Class II Division 1 malocclusion. After analysis, the occlusal contacts were classified according to the established criteria as: tripodism, bipodism, monopodism (respectively, three, two or one contact point with the slope of the fossa); cuspid to a marginal ridge; cuspid to two marginal ridges; cuspid tip to opposite inclined plane; surface to surface; and edge to edge. RESULTS: The mean number of occlusal contacts per subject in Class I malocclusion was 43.38 and for Class II Division 1 malocclusion it was 44.38, this difference was not statistically significant (p>0.05). CONCLUSIONS: There is a variety of factors that influence the number of occlusal contacts between a Class I and a Class II, Division 1 malocclusion. There is no standardization of occlusal contact type according to the studied malocclusions. A proper selection of occlusal contact types such as cuspid to fossa or cuspid to marginal ridge and its location in the teeth should be individually defined according to the demands of each case. The existence of an adequate occlusal contact leads to a correct distribution of forces, promoting periodontal health.